Parents of ataxia-telangiectasia patients display a distinct cellular immune phenotype mimickingATM-mutated patients - ÖZEN, AHMET OĞUZHAN; KOLUKISA, BURCU; AYDINER, ELİF; UYAR, EMEL; ÖĞÜLÜR, İSMAİL; BARIŞ, SAFA (WILEY, 2021)
Background Heterozygous relatives of ataxia-telangiectasia (AT) patients are at an increased risk for certain AT-related manifestations. We also show that there is an increase of infection frequency in parents of AT patients. Thus, we hypothesized that the parents might exhibit immune alterations similar to their affected children. Methods Lymphocyte phenotyping to enumerate T- and B-cell subsets was performed. Functional analyses included in vitro quantified gamma-H2AX, poly (ADP-ribose) polymerase (PARP) and caspase-9 proteins. Chromosomal instability was determined by comet assay. Results We analyzed 20 AT patients (14F/6M), 31 parents (16F/15M), and 35 age-matched healthy controls. The AT patients' parents exhibited low frequency of naive CD4(+)T- (n = 14, 45%) and recent thymic emigrants (n = 11, 35%) in comparison with the age-matched healthy donors. Interestingly, parents with low naive T cells also demonstrated high rate of recurrent infections (9/14, 64%). In comparison with age-matched controls, parents who had recurrent infections and low naive T cells showed significantly higher baseline gamma-H2AX levels and H2O2-induced DNA damage as well as increased cleaved caspase-9 and PARP proteins. Conclusion Parents of AT patients could present with recurrent infections and display cellular defects that mimic AT patients. The observed immunological changes could be associated with increased DNA double-strand breaks.
Keywords: ataxia-telangiectasia; DNA strand breaks; infection; lymphocyte subsets; oxidative stress; parents; RADIATION-INDUCED APOPTOSIS; DNA-DAMAGE; CANCER-RISK; ATM; HETEROZYGOTES; DEFICIENCY; CLEAVAGE; ROLES; GENE